Factors Affecting Visitor Interest to Visit Bhakti Alam as Ecotourism Destination in Pasuruan, East Java - Alfian, Alfian; Soelistyono, Roedy; Nugroho, Iwan (Graduate School, Universitas Brawijaya, 2017)
The aim of the study was to identify factors affecting the decision making of the tourists' interest to visit Bhakti Alam. This study was conducted in Bhakti Alam as one of the ecotourism destination in Tutur, Pasuruan. A set of questionnaire was set up and distributes to 100 visitors in Bhakti Alam on August 2016. In this research, to generate information regarding visitor perception, a series of interview was done. Data was analyzed using multiple linear regression analysis. The research result shows that variables of advertising, public relations, personal marketing, and sale promotion have significant impact on the visiting decision to Bhakti Alam. This condition also supported by determination coefficient value as 0.608. It means that 60.84% variables about visiting decision can be explained by decision-making factors, while the rest of 39.16% explained by another variable that is not being tested. Variables analysed with T test to advertising, public relations, personal marketing, and sale promotion each partially have a significant impact to visiting decision. The multiple linear result analysis showed that between those free variables and visiting decision has a strong connection. The resulting distribution of respondents answer by Likert analysis showed that variable which has the biggest impact started from sale promotion followed by public relations, personal selling, and advertising. While visiting decision more determined by representative location factor, followed by representative condition, access road, price and products. Therefore it means that environment aspect must be maintained and improved. Keywords: Advertising, Bhakti Alam Pasuruan, Ecotourism, Personal Marketing, Public Relations, Sale Promotion.